The effects of neurogranin knockdown on SERCA pump efficiency in soleus muscles of female mice fed a high fat diet - Braun, Jessica L.; Ryoo, Jisook; Goodwin, Kyle; Copeland, Emily N.; Geromella, Mia S.; Baranowski, Ryan W.; MacPherson, Rebecca E. K.; Fajardo, Val A. (Frontiers in Endocrinology, 2022)
The sarco(endo)plasmic reticulum Ca2+ ATPase (SERCA) pump is responsible for the transport of Ca2+ from the cytosol into the sarcoplasmic reticulum at the expense of ATP, making it a regulator of both muscle relaxation and muscle-based energy expenditure. Neurogranin (Ng) is a small protein that negatively regulates calcineurin signaling. Calcineurin is Ca2+/calmodulin dependent phosphatase that promotes the oxidative fibre type in skeletal muscle and regulates muscle-based energy expenditure. A recent study has shown that calcineurin activation reduces SERCA Ca2+ transport efficiency, ultimately raising energy expenditure. Since the biomedical view of obesity states that it arises as an imbalance between energy intake and expenditure which favours the former, we questioned whether heterozygous Ng deletion (Ng+/-) would reduce SERCA efficiency and increase energy expenditure in female mice fed a high-fat diet (HFD). Young (3–4-month-old) female wild type (WT) and Ng+/- mice were fed a HFD for 12 weeks with their metabolic profile being analyzed using metabolic cages and DXA scanning, while soleus SERCA efficiency was measured using SERCA specific Ca2+ uptake and ATPase activity assays. Ng+/- mice showed significantly less cage ambulation compared to WT mice but this did not lead to any added weight gain nor changes in daily energy expenditure, glucose or insulin tolerance despite a similar level of food intake. Furthermore, we observed significant reductions in SERCA’s apparent coupling ratio which were associated with significant reductions in SERCA1 and phospholamban content. Thus, our results show that Ng regulates SERCA pump efficiency, and future studies should further investigate the potential cellular mechanisms.